Pengaruh Model Pembelajaran Eksperiensial dan Gaya Berpikir Terhadap Kemampuan Siswa Dalam Memecahkan Masalah Lingkungan Studi Eksperimen di SMPN 21 Kota Bekasi - Budiaman, Budiaman (Parameter, 2015)
This study aims to determine the effect model of learning and thinking styles of the student's ability in solving environmental problems. This study uses experimental results showed that: First, the ability of students to solve environmental problems learning with instructional strategies ekperiensial higher than students who use expository. Second, the ability of students to the thinking styles accommodating in solving environmental problems is higher than the students' thinking styles assimilative. Third, the interaction between learning strategy and thinking styles affect the ability of students to solve environmental problems. That is the effect of the interaction between learning strategy and thinking styles affect on the level of students' ability to solve environmental problems. Fourth, the ability of students to solve environmental problems have a learning style accommodating with experiential learning strategy is higher than students who studied with expository learning strategy. Fifth, the student's ability to solve the environmental problems that have assimilative learning styles with learning strategies expository higher than students who study with experiential learning strategies. The conclusion from this study is that students who were learning with experiential learning model has the ability to solve environmental problems is higher compared with that get ekpositori learning.